Adaptations and patient responses to behavioral intervention components in a depression-focused chronic disease care model implemented in India. Issue 1 (3rd February 2020) - Johnson, Leslie C M; Chwastiak, Lydia; Poongothai, Subramani; Tandon, Nikhil; Anjana, Ranjit Mohan; Aravind, Sosale; Sridhar, Gumpeny Ramachandra; Rao, Deepa; Mohan, Viswanathan; Ali, Mohammed K
Abstract : Adapting care approaches for patients with diabetes and depressive symptoms in India improved patient-provider communication and patient satisfaction and engagement with care. Abstract: Integrated care models offer one approach to treat patients with chronic multimorbidity. However, because these models consist of multiple components designed to provide individualized care, they should be adapted to best meet the needs of patients in diverse settings. This paper presents qualitative and quantitative data from a realist process evaluation embedded in the INtegrating DEPrEssioN and Diabetes treatmENT (INDEPENDENT) study to uncover what worked, for whom, how, and in what circumstances. We aimed to examine adaptations made to a care coordinator-led behavioral intervention, and how patients responded to adaptations, through a secondary analysis of these data. A purposive sample of 62 patients and 3 care coordinators were recruited based on their involvement with the INDEPENDENT care model across two clinics. Patients were interviewed and surveyed about their experiences in the care model and care coordinators were interviewed about their experiences implementing intervention components. Interview data were coded for reported modifications in intervention content, tools, and delivery; then, these adaptations were categorized by how they served to enhance implementation in the Indian context. Adaptations made in the delivery of this care model served two functions: (a) to improve health promotion communication between care coordinators and patients and (b) to improve patient engagement. Patients' expressed needs were consistent with what care coordinators perceived. Patients were satisfied with adaptations designed to improve intervention fit for local contexts. Study findings demonstrate that adapting components of an integrated care model can enhance patient satisfaction and engagement with behavioral interventions.